Legendary Xinjiang - Huang, Shiyuan ("Charming Xinjiang" series, 2014)
This book guides readers to learn the traditional epic poetry, folk songs, dances and crafts in the form of cultural essays from the first-person perspective. Readers seem to get closer to the local folk customs featured by singing and dancing.